A continuous mental task decreases the physiological response to soccer-specific intermittent exercise. Issue 12 (21st May 2007) - Greig, Matt; Marchant, David; Lovell, Richard; Clough, Peter; McNaughton, Lars
Abstract : Background: Epidemiological findings of higher injury incidence during the latter stages of soccer match-play have been attributed to fatigue. Objective: To examine the interaction of physical and cognitive responses during soccer-specific intermittent exercise. Method: Ten semi-professional soccer players completed a 90-minute laboratory-based treadmill protocol replicating the activity profile of soccer match-play. Two separate trials were performed in randomised order, with and without the added stressor of a continuous grid-based vigilance task. The exercise task comprised six repetitions of a 15 minute activity profile, separated by a passive 15 minute half-time interval. The vigilance task required continual attention and sporadic target response within a letter grid. Physical response (RPE, heart rate, blood lactate, salivary cortisol) and cognitive performance (response time, response accuracy) were quantified at 15 minute intervals. Results: Completing the exercise task with the vigilance task resulted in decreased physiological (heart rate, blood lactate) response. This may be attributed to externally directed attention, resulting in association with the cognitive task and subsequent dissociation from the physical effort. Response speed generally improved with exercise duration, while there was evidence of impaired accuracy in the early stages of the first half and the latter stages of the second half. Conclusion: The interaction of physical and mental work was not additive in nature. The mental task had a masking effect on the physical response. Performing physical exercise tasks without due regard for appropriate psychological stimuli may therefore overestimate the physiological response.